Borrelia bavariensis: Vector Switch, Niche Invasion, and Geographical Spread of a Tick-Borne Bacterial Parasite - Margos, Gabriele; Fingerle, Volker; Reynolds, Stuart (Frontiers in Ecology and Evolution, 2019)
The Borrelia burgdorferi sensu lato species complex currently consists of more than 20 species that utilize small vertebrate hosts as reservoirs and ticks of the genus Ixodes as vectors. The bacterial parasite species differ in their ecology (reservoir hosts, competent vectors) as well as geographical distribution. Several studies have defined reservoir host association as a driver for diversification, speciation and pattern of spatial occurrence of populations but in this review we focus on vector association and its role in diversification and speciation of Borrelia. Borrelia bavariensis, a member of the species complex, uses small mammals as reservoir hosts and can cause Lyme borreliosis in humans. Phylogeographic analysis employing both genetic and genomic data shows that this species has undergone a recent range expansion, invading Europe from its probable original range in Asia while undergoing a drastic genetic bottleneck, suggesting that the colonization of Europe was a single event. We hypothesize that this invasion-like range expansion coincided with a change in the parasite's tick vector, switching from Ixodes persulcatus in Asia to I. ricinus in Europe. Making extensive use of the ecological concept of niche, we discuss the importance of host and vector associations in defining spatial range and their possible role in speciation in the B. burgdorferi sensu lato species complex.